2008
DOI: 10.1136/jme.2007.020750
|View full text |Cite
|
Sign up to set email alerts
|

The views of cancer patients on patient rights in the context of information and autonomy

Abstract: There are extensive efforts in Turkey towards making patient rights a significant supportive component of health services. For patient rights to become a natural part of medical practice it is necessary to give priority to education of both patients and physicians about patient rights and to lay emphasis on an ethical approach in the patient-physician relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 18 publications
0
31
0
7
Order By: Relevance
“…Zamani et al, in 2011, assessed the perspectives of cancer patients and their attending physicians and reported that 88% of patients and 90% of physicians were in favor of telling the truth to cancer patients in the first place; 78% of patients and 72% of physicians be-lieved that the truth must be told to end-stage cancer patients as well (1). In a study by Erer et al on cancer patients, conducted during year 2008, 86.5% of participants believed that the patients have the right to know the truth and treatment; 76.9% believed that physicians must disclose the truth to patients (5). These results indicate a great change in professional behavior about disclosing the truth to patients (6).…”
Section: Introductionmentioning
confidence: 83%
“…Zamani et al, in 2011, assessed the perspectives of cancer patients and their attending physicians and reported that 88% of patients and 90% of physicians were in favor of telling the truth to cancer patients in the first place; 78% of patients and 72% of physicians be-lieved that the truth must be told to end-stage cancer patients as well (1). In a study by Erer et al on cancer patients, conducted during year 2008, 86.5% of participants believed that the patients have the right to know the truth and treatment; 76.9% believed that physicians must disclose the truth to patients (5). These results indicate a great change in professional behavior about disclosing the truth to patients (6).…”
Section: Introductionmentioning
confidence: 83%
“…Ülkemizde kanser hastalarıyla yürütülen bir çalışmada hastaların %86,5'i bilgilenme hakkı olduğunu, %92,3'ü hekimin kendilerini tanı ve tedavi seçenekleri hakkında bilgilendirmesi gerektiğini, %78,8'i hastanın tedavisi hakkında verilen kararlara katılması ve izin alınması gerektiğini, %43,3'ü de hekim tarafından önerilen tedaviyi reddetme hakkı bulunduğunu bildirmişken (12); başka bir çalışmada, onkoloji uzmanlarının kanser hastalarına tanıyı söylemediği ve hastaların karar sürecine katılmadığı bildirilmektedir (13).…”
Section: Introductionunclassified
“…Aynı çalışmada hekim ve hastaların büyük çoğunluğunun hekim yardımlı intihara karşı olduğu; hekim ve hastalar tarafından, aile ve hekim otoritesinin hastanın özerkliğine tercih edildiği gösterilmiştir (14 (8,12). Aynı zamanda verilen eğitimin etkinliği ve teorik bilginin davranışlara yansımasının değerlendirilmesi de önemlidir.…”
Section: Introductionunclassified
“…Universally, recent survey data of patient preferences demonstrate substantial heterogeneity of preferences that are not individually predictable by geography, culture, age, race, sex or educational level [11][12][13][14][15][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]39]. Furthermore, studies that have evaluated the concordance between patient preferences on one hand and family member perception of patient preferences on the other hand have demonstrated that family members commonly underestimate the amount of information that patients desire about their condition and the degree to which they want to be involved in decisionmaking [32,37,[40][41][42][43][44].…”
mentioning
confidence: 99%
“…Although patients vary in the degree to which they want to be medically informed and to thereby participate in the decision-making process, surveys of patient preferences indicate that the overwhelming majority of patients in Western countries [11][12][13][14][15][16][17][18][19], and substantial proportion of patients in nonWestern countries [13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], want disclosure of information to participate in the decision-making process. Universally, recent survey data of patient preferences demonstrate substantial heterogeneity of preferences that are not individually predictable by geography, culture, age, race, sex or educational level [11][12][13][14][15][19][20][21][22][23][24][25][26][27][28][29][30]…”
mentioning
confidence: 99%